Catecholaminergic Crisis After a Bleeding Complication of COVID-19 Infection: A Case Report - Rebollo-Román, Angel; Alhambra-Expósito, Maria R.; Herrera-Martínez, Yiraldine; Leiva-Cepas, F.; Alzas, Carlos; Muñoz-Jiménez, Concepcion; Ortega-Salas, R.; Molina-Puertas, María J.; Gálvez-Moreno, Maria A.; Herrera-Martínez, Aura D. (Frontiers in Endocrinology, 2021)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) presents in some cases with hemostatic and thrombotic complications. Pheochromocytomas are unusual, though potentially lethal tumors. Herein we describe the first case of hemorrhage in a pheochromocytoma related to SARS-CoV-2 infection. A 62-year-old man consulted for syncope, fever and palpitations. He was diagnosed with SARS-CoV-2 pneumonia and presented with a hemorrhage in a previously unknown adrenal mass, which resulted in a catecholaminergic crisis. Medical treatment and surgery were required for symptoms control and stabilization. We hereby alert clinicians to watch for additional/unreported clinical manifestations in COVID-19 infection